Spatially Resolved Elemental Analysis, Spectroscopy and Diffraction at the GSECARS Sector at the Advanced Photon Source. Issue 6 (1st November 2017) - Sutton, Stephen R.; Lanzirotti, Antonio; Newville, Matthew; Rivers, Mark L.; Eng, Peter; Lefticariu, Liliana
Abstract : X‐ray microprobes (XRM) coupled with high‐brightness synchrotron X‐ray facilities are powerful tools for environmental biogeochemistry research. One such instrument, the XRM at the Geo Soil Enviro Center for Advanced Radiation Sources Sector 13 at the Advanced Photon Source (APS; Argonne National Laboratory, Lemont, IL) was recently improved as part of a canted undulator geometry upgrade of the insertion device port, effectively doubling the available undulator beam time and extending the operating energy of the branch supporting the XRM down to the sulfur K edge (2.3 keV). Capabilities include rapid, high‐resolution, elemental imaging including fluorescence microtomography, microscale X‐ray absorption fine structure spectroscopy including sulfur K edge capability, and microscale X‐ray diffraction. These capabilities are advantageous for (i) two‐dimensional elemental mapping of relatively large samples at high resolution, with the dwell times typically limited only by the count times needed to obtain usable counting statistics for low concentration elements, (ii) three‐dimensional imaging of internal elemental distributions in fragile hydrated specimens, such as biological tissues, avoiding the need for physical slicing, (iii) spatially resolved speciation determinations of contaminants in environmental materials, and (iv) identification of contaminant host phases. In this paper, we describe the XRM instrumentation, techniques, applications demonstrating these capabilities, and prospects for further improvements associated with the proposed upgrade of the APS. Core Ideas: X‐ray microprobes are powerful tools for environmental biogeochemistry. Upgraded GSECARS XRM operates down to the sulfur K edge. Capabilities: spatially resolved elemental analysis, spectroscopy, and diffraction. Advanced Photon Source upgrade will further advance XRM capabilities.